Conservation vs. equity: Can payments for environmental services achieve both? - Miriam Vorlaufer; Marcela Ibanez; Bambang Juanda; Meike Wollni (GOEDOC, Dokumenten- und Publikationsserver der Georg-August-Universität, 2015)
This paper investigates the trade-off between conservation and equity considerations in the use of payments for environmental services (PES) that implicitly incorporate different distributive justice principles. Using a public good experiment with heterogeneous participants, we compare the effects on additional area conserved and distribution of earnings of two PES schemes: an equal payment and a payment based on Rawls distributional principle, which we refer to as maxi-min payment scheme. The main findings of the framed field experiment conducted in Jambi province (Indonesia) indicate that the introduction of a maxi-min PES scheme can function as a multi-purpose instrument. It realigns the income distribution in favor of low-endowed participants and does not necessarily need to be compromised by lower environmental additionality at the group level.
urn:nbn:de:gbv:7-webdoc-3962-8
Keywords: 330; Payments for Environmental Services; efficiency equity trade-off; public good experiment; endowment heterogeneity; productivity heterogeneity